Epidemiological Investigation and Genetic Analysis of Duck Circovirus in Korea from 2013 to 2022 - Cheng-Dong Yu; Sang-Won Kim; Cun-Xia Liu; Yue-Hua Gao; Yu-Feng Li; Jong-Yeol Park; Se-Yeoun Cha; Hyung-Kwan Jang; Min Kang; Bai Wei (Animals)
Duck circovirus (DuCV) infections cause immunosuppression in ducks, potentially leading to significant economic losses for the duck farming industry. This study investigates the prevalence, genetic characteristics, and evolutionary trends of DuCV in Korea between 2013 and 2022. Samples from 184 farms across seven provinces were analyzed using polymerase chain reaction (PCR). The overall DuCV infection rate was 29.4% (54/184), with Jeollanam-do showing the highest prevalence (37.5%, 15/40). Ducks aged 3–6 weeks were most susceptible to infection, while ducklings younger than one week were rarely infected. Whole-genome sequencing was performed on 24 positive samples with phylogenetic analysis revealing that DuCV-1b is the predominant subtype in Korea (23/24 strains). Notably, a Korean DuCV-1a subtype strain was identified for the first time, showing close genetic relatedness to Chinese DuCV 1a strains. Novel subtype-specific amino acid variations in ORF1 and ORF2 were statistically analyzed and classified. Recombination analysis suggested some Korean DuCV-1b strains may have resulted from recombination events involving strains from different countries. This comprehensive study provides crucial insights into the current prevalence, genetic diversity, and evolutionary dynamics of DuCV in Korea, offering valuable data for developing effective control strategies and understanding the global epidemiology of this economically important avian pathogen.